Pre-insolvency mechanisms in Portugal: an empirical analysis of their main procedural features - Pinto-Ferreira, J.P.; Gouveia, Mariana França; Santos, S.; Vicente, M.; Seromenho, A. (7th Global Meeting on Law & Society, 2022)
The paper’s goal is to describe some of the core procedural features of the two main judicial pre-insolvency mechanisms in Portugal. We will focus on the special procedure for revitalization – PER (for companies) and on the special procedure for a payment agreement – PEAP (mainly directed at natural persons). We will consider variables such as (1) whether PER and PEAP are mainly used for negotiating an agreement or for obtaining the judicial certification of a previously obtained agreement; (2) the type of judicial intervention and the grounds for such intervention; (3) the average time between the main procedural benchmarks; (4) the more frequent outcomes of PER and PEAP. This analysis will allow us to have a better understanding of PER and PEAP in practice and to identify the main similarities and differences between cases involving companies and natural persons. Currently, the official statistical data is limited in scope since it mainly focuses on the number of PER and PEAP issued and closed and on their average duration. We expect to provide a wide array of concrete data that can be used for policy-making purposes and to inform discussion between specialists on this field. The research will be based on 457 PER and 319 PEAP. This sample represents 7% of the total pre-insolvency proceedings concluded in Portuguese courts between October 2014 and September 2020 and includes all the judicial districts. The data on the variables identified in (1) to (4) and on many other variables has already been collected and is currently being analysed. This work is a part of the research project “Insolvency Law in Portugal: A Multidisciplinary Analysis (IN_SOLVENS)” which will deal with the duration and use of insolvency proceedings and pre-insolvency mechanisms.